C. elegans AP-2 and Retromer Control Wnt Secretion by Regulating MIG-14/Wntless - Pan, Chun-Liang (2007)
While endocytosis can regulate morphogen distribution, its precise role in shaping these gradients is unclear. Even more enigmatic is the role of retromer, a complex that shuttles proteins between endosomes and the Golgi apparatus, in Wnt gradient formation. Here we report that DPY-23, the C. elegans μ subunit of the clathrin adaptor AP-2 that mediates the endocytosis of membrane proteins, regulates Wnt function. dpy-23 mutants display Wnt phenotypes, including defects in neuronal migration, neuronal polarity and asymmetric cell division. DPY-23 acts in Wnt-expressing cells to promote these processes. MIG-14, the C. elegans homolog of the Wnt-secretion factor Wntless, also acts in these cells to control Wnt function. In dpy-23 mutants, MIG-14 accumulates at or near the plasma membrane. By contrast, MIG-14 accumulates in intracellular compartments in retromer mutants. Based on our observations, we propose that intracellular trafficking of MIG-14 by AP-2 and retromer plays an important role in Wnt secretion.